2005
DOI: 10.1007/s11095-005-2593-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Particle Size of Nanospheres and Microspheres on the Cellular-Association and Cytotoxicity of Paclitaxel in 4T1 Cells

Abstract: Cell-association of paclitaxel increased in 4T1, Caco-2, and Cor-L23/R as particle size increased. Paclitaxel delivered from 1-mum microspheres was thrice more cytotoxic to 4T1 cells compared to the drug delivered from nanospheres or solution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 54 publications
0
13
0
Order By: Relevance
“…It is unlikely that the fragments were endocytosed by the cell because the large fragment sizes of 3 – 6 μm are difficult for these cells to endocytose. [37]…”
Section: Resultsmentioning
confidence: 99%
“…It is unlikely that the fragments were endocytosed by the cell because the large fragment sizes of 3 – 6 μm are difficult for these cells to endocytose. [37]…”
Section: Resultsmentioning
confidence: 99%
“…Chakravarthi and coworkers13,19,20 reported that small particles (∼1 μm) could be adsorbed onto the cell surface and thus enhance the therapeutic efficiency. In our studies, we noted that the fluorescent probe and the microparticles did not interact with the cells (the pictures are not shown).…”
Section: Resultsmentioning
confidence: 99%
“…As the endocytosis for NPs was inevitable and the particle size of the NPs was in the range of 200-400 nm in our experiments, the possible mechanism of the limited endocytosis may be attributed to the macropinocytosis. 42 Chakravarthi and coworkers 13,19,20 reported that small particles (∼1 :m) could be adsorbed onto the cell surface and thus enhance the therapeutic effi-ciency. In our studies, we noted that the fluorescent probe and the microparticles did not interact with the cells (the pictures are not shown).…”
Section: In Vitro Cellular Interactions Of Nps and Mpsmentioning
confidence: 99%
See 1 more Smart Citation
“…The less negative value of the other systems (PLA and PCL) was due to the higher molecular weight of polymers. Increase in polydispersity indicates poor stability of the dispersion as observed by the presence of turbidity [30]. Overall, the negative charge leads to strong repellent interactions among the nanoparticles (ANP-10, ANL-10 and ANC-10) in dispersion and thus high stability, did not aggregate upon storage for longer period.…”
Section: Zeta Potentialmentioning
confidence: 99%